The model of economic integration as a pattern of integration of business systems – the concept and interpretation - Rosińska-Bukowska, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The purpose of this article is to present the concept of business integration model, similar to the classic Balassa’s model, as a form of development scheme, which is used not only by the state but also other actors – transnational corporations (TNCs). The article is divided into six parts. The first and second parts – the deepening of the integration process as a response participants of global market about the challenges of globalization and liberalization. The third part – the concept of business integration model (the genesis, the concept, elements). The fourth part – the interpretation of business integration model (theoretical background with using several economic theories). The fifth and sixth parts – the implementation of business integration model in practice. The author shows case studies for Volkswagen (automotiv, Germany), Pfizer (pharmaceutical, USA) and British Petroleum (petrochemical, United Kingdom).